Validation of Stenus (Hypostenus) primivenatus and Stenus (Hypostenus) yiae (Coleoptera, Staphylinidae, Steninae) - Zhao, Cai-Yun; Zhou, Hong-Zhang (Zootaxa, 2020)
Holotype depository was not indicated for the new species, Stenus (Hypostenus) primivenatus and Stenus (Hypostenus) yiae, described as new in the publication Zhao & Zhou (2008). Missing this important message made these two species-group names unavailable according to the fourth edition of the International Code of Zoological Nomenclature (the Code, ICZN, 1999: Article 16.4). This problem was first denoted by Schülke, M. & Smetana, A. (2015).